Effect of low temperature stress on betel vine (Piper betle L.) types, Bangia and Desavari - Kumar, Rajesh Tripathi, Garima Khare, Nikhil (Journal of Spices and Aromatic Crops, 2000)
The effect of low temperature stress was studied in two types (Bangia and Desavari) of betel vine (Piper betle). Among the two types, Desavari showed better performance under cold stress and had significantly higher leaf thickness, levels of total thiols and peroxidase activity and lower lipid peroxidation.